Access to Cyclic α‐CF3‐Substituted α‐Amino Acid Derivatives by Ring‐Closing Metathesis of Functionalized 1, 7‐Enynes. Issue 24 (10th July 2013) - Mailyan, Artur K.; Krylov, Ivan M.; Bruneau, Christian; Dixneuf, Pierre H.; Osipov, Sergey N.
Abstract: An efficient method for the preparation of new α‐CF3 α‐amino acid 1, 7‐enynes that contain electron‐donating and electron‐withdrawing groups on the triple bond has been developed that proceeds through a Sonogashira‐type coupling reaction. The ring‐closing enyne methathesis (RCEYM) of the obtained 1, 7‐enynes with commercially available Grubbs and Hoveyda catalysts provides access to a series of new cyclic α‐amino acids. The latter compounds that contain the 1, 3‐diene moiety are attractive building blocks for the construction of trifluoromethylated polycyclic systems. Abstract : An efficient method to prepare new α‐CF3 α‐amino acid 1, 7‐enynes that contain different substituents on the triple bond has been developed that proceeds by a Sonogashira‐type coupling reaction. The ring‐closing enyne methathesis (RCEYM) of the obtained 1, 7‐enynes with commercially available Grubbs and Hoveyda catalysts provides access to a series of new cyclic α‐amino acids.